2022
DOI: 10.1155/2022/4629392
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential WSB1 Inhibitors by AlphaFold Modeling, Virtual Screening, and Molecular Dynamics Simulation Studies

Abstract: WD40 repeat and SOCS box containing 1 (WSB1) consists of seven WD40 repeat structural domains at the N-terminal end and one SOCS box structural domain at the C-terminal end. WSB1 promotes cancer progression by affecting the Von Hippel–Lindau tumor suppressor protein (pVHL) and upregulating hypoxia inducible factor-1α (HIF-1α) target gene expression. However, the crystal structure of WSB1 has not been reported, which is not beneficial to the research on WSB1 inhibitors. Therefore, we focused on specific small m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Performance is likely to be limited by the availability of an adjacent holo template in the PDB. Chen et al performed short MD simulations prior to virtual screening with docking to identify potential WSB1 inhibitors. Ray and co-workers explored the retrospective FEP performance on AF2 models, using Schrödinger’s FEP+ package, together with a popular benchmark data set for evaluating the performance of FEP implementations.…”
Section: Introductionmentioning
confidence: 99%
“…Performance is likely to be limited by the availability of an adjacent holo template in the PDB. Chen et al performed short MD simulations prior to virtual screening with docking to identify potential WSB1 inhibitors. Ray and co-workers explored the retrospective FEP performance on AF2 models, using Schrödinger’s FEP+ package, together with a popular benchmark data set for evaluating the performance of FEP implementations.…”
Section: Introductionmentioning
confidence: 99%
“…This docking study ccap targets and selects active sites for targeted docking. PyMOL 2.3.0 was utilized to visualize the processed proteins and docking results [39,40].…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that the limitations in benchmarking are not due to the AlphaFold structures itself, but to the methods to accurately model the protein-ligand interactions [27]. Other studies have identified potential inhibitors of WD40 repeat and SOCS box containing 1 protein (WSB1), a clinically relevant drug target, by means of AlphaFold and virtual screening approaches [28].…”
Section: Structural Data Determinationmentioning
confidence: 99%